ROLE OF STANDARDS IN QUALITY MANAGEMENT OF ELECTRONIC EDUCATIONAL RESOURCES (Journal of Information Technologies in Education (ITE), 2013)
Results of the analysis of a role of standards in a quality management system of electronic educational resources (EER) university are presented. Requirements and specifications, methods and technologies of use of standards for definition of criteria, the organizing and carrying out of monitoring of quality EER are described. The offered model of use of standards at carrying out of monitoring of quality EER at the Kherson State University is illustrated on an example of electronic resources for distance learning system «Kherson Virtual University».
Keywords: standards; electronic educational resources; metrics and criteria of quality; quality monitoring; distance learning